Bipartite medial cuneiform: a potential cause of midfoot pain - case report - Helena Ilha, Thales Augusto de Santa; Veiga Sanhudo, Jose Antonio; Pires Veiga Sanhudo , Marina; Parisotto Wisintainer , Maria Eduarda (Journal of the Foot & Ankle, 2023)
Bipartite medial cuneiform is a rare variant of the tarsal bones. The condition can be a potential source for non-traumatic midfoot pain and a possible misdiagnosis cause of several foot disorders, such as the anterior and posterior tibialis tendon disorder. We present the case of a patient with midfoot pain with signs and symptoms suggestive of tibialis anterior tendinopathy. Imaging tests, however, elucidated a bipartite medial cuneiform. The conservative treatment using a removable boot for six weeks effectively relieved symptoms, temporarily promoting pain and limp-free gait, but symptoms relapsed were observed at the last visit.